MANIPULATION AND PUBLIC RELATIONS ETHICS IN THE FILM THANK YOU FOR SMOKING: ANALYSIS OF PROFESSIONAL CODE OF ETHICS VIOLATIONS - Rizky Nabilah Putri; Abdul Rasyid (Journal Analytica Islamica, 2025)
This study analyzes manipulation and ethical violations in Public Relations (PR) as depicted in the film Thank You for Smoking (2005). The film highlights how a tobacco industry spokesperson employs persuasive communication strategies that contradict core PR ethics. This research applies qualitative content analysis using critical discourse and Roland Barthes' semiotic approach. Data were collected through observation of scenes involving manipulation, conflicts of interest, and dishonesty. The findings reveal manipulative practices such as card stacking and issue framing used to shape public opinion. The study concludes that the film serves as a critique of unethical PR practices and emphasizes the urgency of enforcing ethical standards to maintain professional integrity.